What drives nutrition policy reform in Africa? Findings of a Three-Country Case Study Comparison (Malawi, South Africa, and Zambia) - Hendriks, Sheryl (2017)
Sheryl Hendriks POLICY SEMINAR What Drives Policy Change? Insights from the Kaleidoscope Model of Food Security Policy Organized by IFPRI, Michigan State University and University of Pretoria, Consortium partners- Food Security Policy Innovation Lab